Study on Moisture Management Properties of Eri Silk Knitted Denim Fabrics. Issue 15 (23rd November 2022) - Kumar, T. Sathish; Kumar, M. Ramesh; Prakash, C.
ABSTRACT: This study was aimed to develop knitted denim fabrics by using cotton and eri silk yarns. Three combinations of 3/1 twill knitted denim fabrics were developed. Two materials cotton yarn 30 s and eri silk yarn 2/80 s Nm with three types (100% cotton, 50% cotton/50% eri silk, 100% eri silk) of knitted denim fabrics were produced. Moisture management properties were tested for the developed samples.100% eri silk knitted denim fabric was found with the excellent accumulative one way transport index % and a very good overall moisture management capability better than that of 100% cotton and 50% cotton/50%eri silk knitted denim fabrics. The results indicated that the eri silk knitted denim fabric is more suitable for active wear and functional wear applications.